Beyond structure: emerging approaches to study GPCR dynamics. (August 2020) - Gusach, Anastasiia; Maslov, Ivan; Luginina, Aleksandra; Borshchevskiy, Valentin; Mishin, Alexey; Cherezov, Vadim
Graphical abstract: Highlights: GPCRs are highly dynamic proteins that sample multiple conformational states. Dynamic behavior of GPCRs can be described using the concept of energy landscapes. Understanding signaling mechanisms requires both structure and dynamics. New approaches uncover GPCR dynamics in population and at a single molecule level. Abstract : G protein-coupled receptors (GPCRs) constitute the largest superfamily of membrane proteins that are involved in regulation of sensory and physiological processes and implicated in many diseases. The last decade revolutionized the GPCR field by unraveling multiple high-resolution structures of many different receptors in complexes with various ligands and signaling partners. A complete understanding of the complex nature of GPCR function is, however, impossible to attain without combining static structural snapshots with information about GPCR dynamics obtained by complementary spectroscopic techniques. As illustrated in this review, structure and dynamics studies are now paving the way for understanding important questions of GPCR biology such as partial and biased agonism, allostery, oligomerization, and other fundamental aspects of GPCR signaling.